Complex reaction networks in high temperature hydrocarbon chemistry1. Issue 12 (28th March 2015) - Mutlay, İbrahim; Restrepo, Albeiro
<x xml:space="preserve">Abstract</x> Complex network theory reveals novel insights into the chemical kinetics of high temperature hydrocarbon decomposition.